A novel substitution of proline (P32L) destabilises β2-microglobulin inducing hereditary systemic amyloidosis. (2nd October 2022) - Prokaeva, Tatiana; Joshi, Tracy; Klimtchuk, Elena S.; Gibson, Victoria M.; Spencer, Brian; Siddiqi, Omar; Nedelkov, Dobrin; Hu, Yueming; Berk, John L.; Cuddy, Sarah A. M.; Dasari, Surendra; Chiu, April; et al.
Abstract: Background: β2-microglobulin amyloidosis was first described in the 1980s as a protein deposition disease associated with long-term haemodialysis. More recently, two inherited forms resulting from separate point mutations in the β2-microglobulin gene have been identified. In this report, we detail a novel β2M variant, P32L, caused by a unique dinucleotide mutation that is linked to systemic hereditary β2-microglobulin amyloidosis. Methods: Three family members from a Portuguese kinship featured cardiomyopathy, requiring organ transplantation in one case, along with soft tissue involvement; other involvements included gastrointestinal, neuropathic and sicca syndrome. In vitro studies with recombinant P32L, P32G, D76N and wild-type β2-microglobulin were undertaken to compare the biophysical properties of the proteins. Results: The P32L variant was caused by the unique heterozygous dinucleotide mutation c.154_155delinsTT. Amyloid disease featured lowered serum β2-microglobulin levels with near equal amounts of circulating P32L and wild-type proteins; amyloid deposits were composed exclusively of P32L variant protein. In vitro studies of P32L demonstrated thermodynamic and chemical instability and enhanced susceptibility to proteolysis with rapid formation of pre-fibrillar oligomeric structures by N- and C-terminally truncated species under physiological conditions. Conclusions: This work provides both clinical and experimental evidence supporting the critical role of P32 residue replacement in β2M amyloid fibrillogenesis.